2011
DOI: 10.2166/hydro.2011.059
|View full text |Cite
|
Sign up to set email alerts
|

An artificial intelligence approach for optimizing pumping in sewer systems

Abstract: This paper presents details of a fuzzy logic system developed for the control of sewer pumping stations for energy costs savings. This is part of an ongoing collaborative project between Anglian Water and the University of Sheffield. The model rules and operation are developed for one representative pumping station in order to enable the identification of potential benefits and inhibitors to Anglian Water. Results are included that demonstrate the potential for energy cost-savings by application to a single pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…The application of genetic algorithms to optimise fuzzy sets for sewer pumps at a single pump station was achieved by Ostojin et al (2011). Their work shows that a thorough foundation and fuzzy-based framework could lead to the application of advanced techniques in terms of decision support and ultimately optimisation.…”
Section: Discussionmentioning
confidence: 99%
“…The application of genetic algorithms to optimise fuzzy sets for sewer pumps at a single pump station was achieved by Ostojin et al (2011). Their work shows that a thorough foundation and fuzzy-based framework could lead to the application of advanced techniques in terms of decision support and ultimately optimisation.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial improvement in the availability and ownership cost of instrumentation, data collection, and communications, and the way they are applied will also impact on other distributed infrastructure; for the water sector, this includes sewerage systems. Such work is already underway, for example, on CSO analytics (Guo and Saul, 2011;Mounce et al, 2014) and GA optimised fuzzy logic pump control (Ostojin et al, 2011 Figure 6. Schematic of idealised combined application.…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable growth [8] in this sector could be achieved through several strategies, which aim at an optimal management of water distribution networks. For example, optimal pump scheduling, in both clean water [10][11][12] and drainage [13][14][15][16] pumping systems has been shown to improve energy efficiency. In particular, a recent study [15] showed that an optimal pump scheduling in a drainage system can ensure an average value of recovered energy up to 32%.…”
Section: Introductionmentioning
confidence: 99%